Developing a Collaborative Faculty-Librarian Information Literacy Assessment Project - Belanger, Jackie; Bliquez, Rebecca; Mondal, Sharleen (Emerald Publishing Library Review, 2012)
Purpose – The purpose of this paper is to describe the process of developing an information literacy assessment project, and to discuss key findings from the project. Design/methodology/approach – A variety of assessment tools were used to gather information about student learning and our information literacy instruction: pre- and post-surveys, student feedback surveys, faculty feedback to librarians, librarian self-reflection, library worksheets, student research journals, and citation analysis of students’ final research paper bibliographies. Findings – We found that our initial suite of assessment tools did not provide us with the information we wanted about students’ research processes, so we modified our ‘assessment toolkit’. We found that we were able to gather more meaningful information about students’ research processes when we worked closely with faculty to embed information literacy assessments into course assignments. From our analysis of student work, we discovered that, for many students, our library instruction was most valuable in helping them refine and explore research topics. Originality/value – This paper will be useful to librarians and faculty seeking to implement an information literacy assessment project. We provide ideas for ways for faculty and librarians to collaborate on information literacy assessment, as well as on assignment and course design.
Case study
Keywords: information literacy, assessment, collaboration, higher education, academic libraries